Bibliometric-Systematic Literature Review (B-SLR) Analysis on Youth AI Literacy: Identifying Patterns, Gaps, and Future Research Opportunities - Lutfi, Muhammad (Raden Intan State Islamic University of Lampung, Indonesia, 2026)
The rapid advancement of Large Language Models (LLMs) in the past six years, coupled with widespread adoption of Artificial Intelligence (AI) technologies, necessitates the critical assessment of collective readiness, especially among the youth population. This study aims to examine the coverage of academic literature that addresses key issues in youth AI literacy. To achieve this, a combined methodology of Systematic Literature Review (SLR) using the PRISMA framework and Bibliometric analysis (B-SLR) is undertaken using Scopus-indexed data and software such as Watase Uake, VOSviewer, and Bibliometrix to highlight emerging issues in AI literacy research. Based on the synthesis of 38 journal articles published between 2022-2025 from Q1-Q2 tier, this paper proposes an ABC AI Literacy framework for youth (Algorithmic Acumen, Building & Co-creation, and Critical Consciousness) that explains key aspects of recent AI literacy research. Furthermore, this paper highlights under-researched issues in the literature to inform academics for possible future research directions. These findings urge policymakers, educators, and other stakeholders to support more research in this area, especially in regions such as Africa and Southeast Asia. The main limitation of this study is that the evaluation will rely on qualitative thematic analysis, rather than quantitative analysis.